2012
DOI: 10.1590/s0037-86822012000100014
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of synanthropic triatomines (Hemiptera: Reduviidae) in the Federal District of Brazil

Abstract: This retrospective analysis considered the number of adults and nymphs of each species collected and infected in both intradomicile and peridomicile. Results: A total of 754 triatomines were collected in 252 reported domiciles. Panstrongylus megistus was the most frequent species (65%), followed by T. pseudomaculata (14%). Of the 309 examined insects, only 3 (1%) specimens of P. megistus were infected with flagellates morphologically similar to Trypanosoma cruzi. The spatial occurrence indicated a higher diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
23
0
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 41 publications
3
23
0
10
Order By: Relevance
“…Data on the occurrence of triatomine species in domiciliary environments between 1975-1983 were also taken into account (Silveira et al 1984), as were data from other studies (Silva & Lustosa 1993, Carcavallo et al 1999, 2002, Carcavallo & Jurberg 2000, Oliveira & Silva 2007, Almeida et al 2008, Gurgel-Gonçalves & Silva 2009, Gurgel-Gonçalves et al 2012b, Maeda et al 2012, Obara et al 2012). In addition, records of triatomines in the collections of Rodolfo Carcavallo and Herman Lent at the National and International Reference Laboratory on Triatomine Taxonomy at the Oswaldo Cruz Institute, Oswaldo Cruz Foundation, were analysed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on the occurrence of triatomine species in domiciliary environments between 1975-1983 were also taken into account (Silveira et al 1984), as were data from other studies (Silva & Lustosa 1993, Carcavallo et al 1999, 2002, Carcavallo & Jurberg 2000, Oliveira & Silva 2007, Almeida et al 2008, Gurgel-Gonçalves & Silva 2009, Gurgel-Gonçalves et al 2012b, Maeda et al 2012, Obara et al 2012). In addition, records of triatomines in the collections of Rodolfo Carcavallo and Herman Lent at the National and International Reference Laboratory on Triatomine Taxonomy at the Oswaldo Cruz Institute, Oswaldo Cruz Foundation, were analysed.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, acute cases of human disease caused by transmission via native triatomine species are still being registered (MS/SVS 2012). Triatomines continue to infest homes in a number of states in Brazil (Oliveira & Silva 2007, Almeida et al 2008, Villela et al 2009, Gurgel-Gonçalves et al 2010, Silva et al 2011, 2012, Maeda et al 2012). …”
mentioning
confidence: 99%
“…In our dataset, the two administrative regions with the most reported triatomines in the Federal District were Vicente Pires and Park Way, whereas Maeda et al 6 reported most bugs from the more rural Planaltina and Sobradinho. This suggests that the number of triatomines, particularly P. megistus, found in urbanized environments may have increased over the last few years.…”
mentioning
confidence: 63%
“…In 2002-2010, and using methods comparable to ours, 754 bugs were caught in 20 administrative regions 6 . This suggests that sylvatic foci of synanthropic triatomines persisted in the Federal District, with the bugs (especially P. megistus) regularly invading and at times colonizing human habitats.…”
mentioning
confidence: 75%
See 1 more Smart Citation